Turkey - Country Economic Memorandum : Structural Reforms for Sustainable Growth, Volume 1. Main Report - World Bank (Washington, DC, 2013)
This country economic memorandum shows that fiscal imbalances are key to understanding Turkey's inflation problem, and its volatile growth. Its findings suggest that the country's inability to sustain high growth can be closely linked, among many factors, to the lack of macroeconomic stability. Unsustainable fiscal policy, has put repeated pressure on its currency, and led to chronic, and high inflation. Thus, when facing crises, fiscal policy has been unable to withstand, or influence on the business cycle; instead contractionary policies have been implemented to achieve monetary stability, actually worsening the real impact of shocks. It is also suggested that previous attempts at stabilization, failed precisely because they did not address the structural sources of fiscal deficit. Following an analysis on Turkey's macroeconomic framework, the report reviews the reform agenda on the infrastructure, agriculture, and banking sectors, and the country's medium-term prospects, but emphasizes the influence of the policy environment on total factor productivity growth, as a key explanatory factor, recommending structural policies to generate at least a primary surplus of three percent of GNP, prioritize social security, and social assistance, and avoid unsustainable contingent liabilities, by deregulating energy and telecommunications sectors, and, pursue financial sector reform.